Observation of a new baryon state in the Λ0bπ+π− mass spectrum; Journal of High Energy Physics; Vol. 2020, iss. 6 - Aaij R. Roel; Beteta C. A. Carlos Abellan; Ackernley T.; Adeva B. Bernardo; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich (2020, 2020)
Title screen